Índice glicêmico e carga glicêmica: associação com doenças crônicas não transmissíveis e valores em fórmulas enterais industrializadas - Jéssica Abdo Gonçalves Tosatti (2018)
Introduction: The glycemic index (GI) and glycemic load (GL) are indicators of carbohydrate quality and determinants of postprandial glycemic response. High GI/ GL diets have been associated with increased risk of various non-communicable diseases (NCDs). The GI values of foods are compiled into tables and the GL is calculated from the GI and the amount of carbohydrate available in the portion of food consumed. However, the GI and GL values of enteral formulas commonly used in clinical practice are not included in these tables. Aims: The present dissertation had two main aims: 1. To review the scientific evidence about the role of GI and GL in the risk of NCDs and 2. To determine the GI of enteral formulas commonly used in clinical practice. Methods: Two studies were performed. In order to meet the first aim, an overview of systematic reviews with meta-analysis of observational studies that evaluated the association between GI/ GL and risk of NCDs in healthy adults was conducted through of a search of the scientific literature in PubMed, Cochrane Central and Scopus. The overview protocol was conducted according to Cochrane guidelines, two reviewers performed all steps independently and a standardized data collection form was used to data extraction. The methodological quality of the eligible systematic reviews was assessed by the Assessing the Methodological Quality of Systematic Reviews (AMSTAR) questionnaire and a qualitative analysis of the results was performed. In order to meet the second objective, a randomized clinical trial (RCT) was conducted in which the GI of 10 enteral formulas was determined according to the protocol recommended by the FAO/ WHO, glucose solution as food reference, being offered to each participant the quantity enteral formula and glucose solution equivalent to 25 grams of available carbohydrate. Each participant tested two formulas and the glucose solution, whose order was established at random. The incremental area under the curve (IAUC) of the glycemic response of the enteral formulas and the glucose solution was determined from the trapezoidal rule and the GI was calculated from the IAUC ratio, the value multiplied by 100 for the GI to be expressed as a percentage. The inter-individual coefficient of variation for the GI was determined. Results: 711 articles were identified in the initial search and 22 met the inclusion criteria for the overview. A positive association was observed between the consumption of high GI / CG diets and cardiovascular disease risk [n = 4; high GL (HGL) in all studies, high GI (HGI) in 3 studies], stroke (n = 3; (n = 3, HGL in 2 studies, HGI in all studies), and cancer (n = 11, HGL in 3 studies, HGI in 5 studies). The increased risk of NCDs ranged from 5 to 38%. Forty healthy adults (85% women, 27.07±6.72 years) participated in the RCT for the determination of GI. The GI of the enteral formulas ranged from 35.40% to 94.89%. Four enteral formulas presented HGI (Nutrienteral 1.5®, Novasource GI Control®, Diamax®, Isosource Soya®), two intermediate GI (Fresubin 1.2 HP Fibre®, Nutrison Energy Multifiber 1.5®) and three low GI (Trophic 1.5®, Glucerna®, Novasource GC HP®). Conclusion: According to the overview there is consistent evidence supporting the importance of reducing dietary GI/ GL as an additional strategy to minimize the risk of NCDs considering the positive association observed between HGI/ HGL diets and risk of cardiovascular disease, type diabetes 2, stroke, breast and endometrial cancer. In addition, the GI of enteral formulas commonly used in clinical practice varied between 35 and 95% and this nutritional information should be considered in the dietary prescription of patients in enteral nutritional therapy.